The Gender Trap: Performing Gender and Queerness as Reflected in Pink Peso Advertisements - Ponce, Sherie Claire G. (Philippine Humanities Review; Vol 25 No 1: Philippine Humanities Review (2023-2024): Rebyu ng Arte at Literatura ng Pilipinas, 2025)
Over the past decades, there has been a rise in interests regarding gender and queer studies. Numerous scholars, from Michel Foucault to Judith Butler, have long posited questions that examine heteronormative and hegemonic assumptions. Most gender theorists lay their theoretical foundations based on the premise that gender is fluid, and that gender is not something one possesses (like a physiological or genetic makeup). Rather, gender is dependent upon what one does, a continuous repetition of stylized acts that is attributed to stereotypical notions of masculinity and femininity that is evident within society. Using Judith Butler’s theory of gender performativity, this study focused on the manifestations of gender ideals and identities found within seven pink peso advertisements (advertisements with queer elements and representations that are produced to tap into the LGBTQ+ community and its allies). To examine the societal constructions and collective ascriptions of Filipinos when it comes to gender, this study utilized cluster criticism as its critical approach to delve into the conscious and unconscious norms and expectations of society to non-heteronormative folk. This study discusses the continued use of traditional binaries in the performance of gender, conforming to gender stereotypes in asserting the gender identity and sexual orientation being performed. Gender typecasting, consistently performed and reflected in Philippine advertisements, is further critiqued as it reinforces norms and expectations based primarily on a heteronormative standard, despite being a very fluid concept.